Influence Literacy Finance Shariah and Use Syariah Fintech Lending on the Development of MSMEs - Siregar, Zultri Aulia; Nurbaiti, Nurbaiti; Syahbudi, Muhammad (Pusat P2M Politeknik Negeri Batam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy, including in Medan City. This study aims to analyze the influence of Islamic financial literacy and Islamic fintech lending on the development of MSMEs in Medan City. Islamic financial literacy includes MSME actors' understanding of Islamic financial principles, such as the prohibition of usury and gharar, while Islamic fintech lending is a technology-based financing alternative that is in accordance with Islamic principles. This study uses a quantitative approach with multiple linear regression analysis methods. Data were obtained through questionnaires distributed to 86 MSME actors selected using purposive sampling techniques. The results of the study indicate that Islamic financial literacy significantly affects the ability perpetrator MSMEs in manage finance And determine source appropriate financing. In addition, sharia fintech lending has a significant positive impact on the ability of MSMEs to obtain fast, safe and halal financing. Simultaneously, both variables contribute positively to the development of MSMEs. This finding confirms that collaboration between Islamic financial literacy and financial technology can be an effective solution to overcome the challenges faced by MSMEs.